Successive relaying secure transmission scheme based on inter-relay interference cancellation - Yi ZOU; Kai-zhi HUANG; Xiao-lei KANG (Tongxin xuebao)
A secure scheme based on inter-relay interference cancellation was proposed to solve untrusted relay eavesdropping problem in successive relaying systems.First inter-relay interference between trusted relay and untrusted relay was exploited as artificial noise to degrade untrusted relay’s eavesdropping condition,then interference iterative cancellation was adapted to improve signal quality at legitimate user by making use of correlation between signals in time domain.Based on this,a quick power allocation algorithm aiming to minimize untrusted relay’s sum rate was proposed.Analysis and simulation results show that the proposed scheme suppress untrusted relay’s eavesdropping without loss of communication efficiency,a promotion of at least 2 bit·s-1·Hz-1in secrecy rate can be observed.